Effect of presence of 10-MDP adhesive monomer within the adhesives on improving the bond strength to the metal (In-vitro study) (Journal of Hama University, 2019)
Clinical practice has demonstrated the need for increased adhesion between adhesive and metal alloys, Therefore, adhesion systems have been developed by adding adhesive monomers, which are known to form chemical bonds with various materials. This research aimed to study the effect of presence of 10-MDP adhesive monomer within the adhesion system on improving  the bond strength to the Nickel-chromium alloy.40 metal plates made of nickel-chromium alloy has been designed with dimensions of 10 mm x 10 mm and a thickness of 2.5 mm,Each plate has been sandblasted  50-micron aluminum oxide pellets and  Each two plates were bonded together.Specimens were divided into two equal groups according to the adhesion system:Group (B): 10 pairs of metal plates bonded to gether with 10-MDP containing resin cement Panavia SA Cement plus (kuraray).Group (A): 10 pairs of metal plates bonded to gether with resin cement Variolink N (Ivoclar vivadent) Which does not contain 10-MDP monomer. Samples were kept in distilled water at 37 ° C for 24 hours, And then subjected to cycles of heat in which the temperature between (5-55)°C.shear bond strength tests was applied upon the bonded plates until they were separated. Data (MPa) was analyzed using T-s tests at (α=0.05) significance level.There is statistically significant difference between groups (B) and (A), Where Mean shear bond strength for the group (B) is (15.68) Mpa and group (A) is (4.7) Mpa.Using 10-MDP containing resin cement.increased the strength of the bond.Resin cements with a 10-MDP adhesive monomer are bonded with the nickel-chromium alloy more closely than other cements Because of the chemical bonds formed by 10-MDP monomer with the mineral oxides on the surface of alloy.